Defective nuclear localization of Hsp70 is associated with dyserythropoiesis and GATA-1 cleavage in myelodysplastic syndromes. - Frisan, E; Vandekerckhove, J; de Thonel, A; Pierre-Eugène, C; Sternberg, A; Arlet, J; Floquet, C; Gyan, E; Kosmider, O; Dreyfus, F; Gabet, A; Courtois, G; et al. (2012)
Normal human erythroid cell maturation requests the transcription factor GATA-1 and a transient activation of caspase-3, with GATA-1 being protected from caspase-3-mediated cleavage by interaction with the chaperone heat shock protein 70 (Hsp70) in the nucleus. Erythroid cell dysplasia observed in early myelodysplastic syndromes (MDS) involves impairment of differentiation and excess of apoptosis with a burst of caspase activation. Analysis of gene expression in MDS erythroblasts obtained by ex vivo cultures demonstrates the down-regulation of a set of GATA-1 transcriptional target genes, including GYPA that encodes glycophorin A (GPA), and the up-regulation of members of the HSP70 family. GATA-1 protein expression is decreased in MDS erythroblasts, but restores in the presence of a pan-caspase inhibitor. Expression of a mutated GATA-1 that cannot be cleaved by caspase-3 rescues the transcription of GATA-1 targets, and the erythroid differentiation, but does not improve survival. Hsp70 fails to protect GATA-1 from caspases because the protein does not accumulate in the nucleus with active caspase-3. Expression of a nucleus-targeted mutant of Hsp70 protects GATA-1 and rescues MDS erythroid cell differentiation. Alteration of Hsp70 cytosolic-nuclear shuttling is a major feature of MDS that favors GATA-1 cleavage and differentiation impairment, but not apoptosis, in dysplastic erythroblasts.